Medical and Surgical Abortion in the Second Trimester of Pregnancy - Karki, A; Dangal, G; Pradhan, HK; Shrestha, R; Bhattachan, K (Nepal Journal of Obstetrics and Gynaecology, 2015)
Aims: This study was done to know the demographic profile of women undergoing second trimester abortion at Kathmandu Model Hospital. The aim was to see the success rate of combination of mifeprostone and misoprostol for the medical induction and misoprostol alone for the cervical dilation in case of surgical evacuation. Methods: A retrospective study was done by looking at the profiles of 540 clients on whom second trimester abortion was performed during the period of October 2010 to October 2014. Twenty-nine women underwent dilatation and evacuation (D&E) with misoprostol cervical priming, and 510 underwent medical induction with mifeprostone and misoprostol whereas one client absconded. Furthermore, the reasons for seeking second trimester abortion were also investigated. Results: It can be seen that the age of women undergoing second trimester abortion at Kathmandu Model Hospital was greatest (33.33%) for the age group of 26-30 years. Most women were illiterate (31.67%) and a majority of the women were housewives (89.81%). A greater proportion of the women had never undergone abortion. Mental cause appeared to be the major reason for abortion constituting 82.04%. Success was 90.58%, expulsion with total five doses of misoprostol. The median induction to abortion time was 4-7 hours. The expulsion hours increased as the gestational age increased. The median number of dose of misoprostol required was two for medical induction and three for surgical abortion. Conclusions: Mifeprostone and misoprostol, as combination was a good method for the medical induction of second trimester pregnancy and misoprostol alone for the cervical preparation in surgical evacuation was promising.